Isotope-specific lithium bioactivity – physiological reality or laboratory oddity? - Delacour, Cecile; Deline, Marshall; Hermannsdóttir, Hildigunnur; Lu, Zhaoqi; Gingras, Michel J. P.; Fromme, Tobias (Frontiers in Psychiatry, 2025)
The efficacy of lithium in treating bipolar disorder is well established, yet its precise molecular mechanisms remain elusive. A frequently overlooked dimension is the natural occurrence of two stable lithium isotopes (6Li and 7Li), which differ significantly in mass and nuclear spin and may therefore exhibit distinct bioactivity within living systems. Evidence from multiple rodent studies demonstrates isotope-dependent behaviour effects, suggesting translational relevance. Mechanistic exploration indicates that while classical lithium targets such as glycogen synthase kinase-3 beta and myo-inositol monophosphatase do not discriminate between isotopes, differential effects emerge at the level of mitochondrial calcium handling. Lithium isotopes modulate the calcium storage capacity of brain mitochondria, potentially via incorporation into amorphous calcium phosphate structures, which form crucial calcium depots within the mitochondrial matrix. The physical basis may involve isotope-dependent differences in mass or nuclear spin, possibly interacting with amorphous calcium phosphate or influencing radical pair formation, situating these findings within the rapidly expanding field of quantum biology. However, critical experimental gaps remain, particularly regarding whether isotope-specific mitochondrial effects translate to changes in neuronal signaling. Addressing these gaps through targeted physiological and clinical studies could clarify whether lithium isotope bioactivity is a laboratory curiosity or a tractable quantum biological phenomenon with therapeutic potential.